OTT-messaging and mobile telecommunication: A joint market? - An empirical approach - Nicolas Wellmann (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2017)
OTT-messenger such as facebook, WhatsApp have gained wide popularity among mobile users while traffic of text messaging has been in strong decline in several countries. This work is the first to provide an empirical analysis how consumption of OTT-messengers affects demand for text messaging and mobile telephony services. Our findings suggest that social and messaging apps may complement demand for text messaging and mobile voice services. More generally we identify the different nature of mobile telecommunication services as key element to explain why reductions of text messaging traffic have been so drastic in some countries and why an analogue development for mobile voice is rather unlikely.
Keywords: L96; L43; L51; C33; C36; 330; OTT-messenger; mobile telecommunication; market definition; regulation; mature markets; communication behavior